Natural polysaccharide / aleppo avens positive gingival pasting film with antibacterial property and adhesion and preparation method of natural polysaccharide / aleppo avens positive gingival pasting film
By combining the Blue Bu Zheng drug into a natural polysaccharide matrix, using chitosan quaternary ammonium salts and catechol modified chitosan quaternary ammonium salts, a natural polysaccharide/Blue B Zheng with antibacterial and adhesion was prepared. Gingival patches solve the problem that existing gum patches cannot effectively promote gingival regeneration and repair, and achieve long-term gingival tissue repair and antibacterial effects.
Patent Information
- Application Number
- CN202411393829.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-17
AI Technical Summary
The existing gingival membrane cannot effectively promote gingival regeneration and repair, and the Blue Buzheng drug is not film-forming, cannot prepare film-forming samples, and cannot be released for a long time, resulting in poor gingival repair effect.
Combine the Blue Bu Zheng drug in a natural polysaccharide matrix, and prepare a natural with antibacterial and adhesion by combining chitosan quaternary ammonium salt and catechol modified chitosan quaternary ammonium salt with blue Bu Zheng. Polysaccharide/blue cloth orthogonal gingival film achieves the purpose of adhering to the gingival and releasing the blue cloth, enhancing the regeneration and repair effect of gingival tissue.
The film has excellent antibacterial properties and wet tissue adhesion properties, with an antibacterial rate of 99.9%. The sustained release time of Lanbuzheng drug is up to 12 hours, effectively promoting gingival regeneration and repair, and the asymmetric structure is easy to use in clinical practice and avoiding stickiness Attached to the finger.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a natural polysaccharide / blue cloth orthogingival film with antibacterial and adhesive properties and a preparation method thereof. Background Art
[0002] Gingival recession refers to the exposure of tooth roots caused by the retreat of the gingival margin to the root side of the enamel-bone junction. It is a common oral disease, and more than 50% of people have gingival recession. Severe gingival recession can lead to tooth loss, which has caused great trouble to people's health and life. Therefore, a gingival film is prepared that has good adhesion and antibacterial properties to the gums, and can also promote gum regeneration and repair, which has important clinical application value. Summary of the invention
[0003] The purpose of the present invention is to provide a natural polysaccharide / Lanbuzheng gingival film with antibacterial and adhesive properties and a preparation method thereof, which can compound Lanbuzheng drugs in a natural polysaccharide matrix to make a gingival film, achieve the purpose of adhering to the gums and slowly releasing Lanbuzheng, and the sustained release time can be up to 12 hours, thereby promoting the regeneration and repair of gingival tissue. Chitosan quaternary ammonium salt is generated by the reaction of the epoxy group in the 2,3-epoxypropyl-trimethylammonium chloride molecule with the amino group in the chitosan molecule, and the chitosan quaternary ammonium salt has a good inhibitory effect on the growth of oral bacteria that cause periodontitis, with an antibacterial rate of 99.9%, preventing oral bacteria from further damaging gingival tissue. The carboxyl groups in the 3,4-dihydroxyphenylpropionic acid molecule and the amino groups in the chitosan molecule are linked to the catechol functional groups under the catalytic action of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride to obtain catechol-modified chitosan quaternary ammonium salt (QCCS). Catechol can increase the adhesion of the material to the wet tissue, and the wet bonding strength is ≥10kPa, making the oral film not easy to fall off. After the QCCS / Lanbuzheng aqueous solution is cast, it is dried to a semi-dry state, and then a layer of natural polysaccharide powder is evenly sprinkled on the upper surface of the film, and it is continued to be dried. At this time, the natural polysaccharide-Lanbuzheng oral film has an asymmetric structure. The side without natural polysaccharide powder is easy to adhere to the wet gingival tissue due to the presence of catechol structure, while the side with natural polysaccharide powder can prevent the film from sticking to the fingers during application, which is convenient for clinical use. The asymmetric natural polysaccharide / blue cloth gingival film has excellent wet tissue adhesion, antibacterial properties, drug sustained release properties, and excellent gingival tissue regeneration and repair properties.
[0004] The present invention is implemented by the following technical solutions:
[0005] A method for preparing a natural polysaccharide / blue cloth orthogingival film with antibacterial and adhesive properties, comprising the following steps:
[0006] 1) adding chitosan (CS) powder to an acetic acid aqueous solution with a concentration of 1% to 5%, stirring for 0.5 to 1 hour to prepare a chitosan solution with a chitosan mass concentration of 20-100 mg / ml;
[0007] 2) Weigh a certain amount of 2,3-epoxypropyl-trimethylammonium chloride, dissolve it in deionized water, and add it dropwise to the solution in step 1) above, at 50-80° C., and stir for 6-10 hours;
[0008] 3) placing the reaction product solution in step 2) into a dialysis bag with a molecular weight cutoff of 3000-8000D, dialyzing for 3 days, replacing the dialysate once every 12 hours, and freeze-drying to obtain chitosan quaternary ammonium salt (QCS);
[0009] 4) adding chitosan quaternary ammonium salt to deionized water and stirring for 0.5 to 1 hour to obtain a chitosan quaternary ammonium salt aqueous solution with a mass concentration of 20-100 mg / ml;
[0010] 5) A certain amount of 3,4-dihydroxyphenylpropionic acid (HCA) and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC) are dissolved in deionized water respectively, and the solutions are added to the solution obtained in step 4) in sequence.
[0011] 6) The pH value of the solution obtained in step 5) is adjusted to 5.5 with hydrochloric acid solution, and then stirred at room temperature for 18-24 hours.
[0012] 7) The reaction product solution in step 6) is placed in a dialysis bag with a molecular weight cutoff of 3000-8000D, dialyzed for 3 days, the dialysate is replaced once every 12 hours, and freeze-dried to obtain catechol-modified chitosan quaternary ammonium salt (QCCS);
[0013] 8) Add QCCS and indigoferin into deionized water and stir for 0.5 to 1 hour to prepare a QCCS / indigoferin aqueous solution, wherein the total mass concentration of QCCS and indigoferin is 50-100 mg / ml;
[0014] 9) Pour the solution in 8) into a polytetrafluoroethylene mold (10cm×10cm×2mm), and bake in a 60-80°C oven for 1.5 hours. At this time, the film is in a semi-dry state. Sprinkle a layer of natural polysaccharide powder evenly on the upper surface of the film, and continue to bake in a 60-80°C oven for 4-6 hours to obtain a natural polysaccharide / blue cloth orthogingival film with antibacterial and adhesive properties.
[0015] In the above technical solution, further, the molecular weight of the chitosan is 10,000-1,000,000, and the degree of deacetylation is 70%-95%.
[0016] Furthermore, the mass ratio of the 2,3-epoxypropyl-trimethylammonium chloride to chitosan is 0.6:1 to 2:1.
[0017] Furthermore, the mass ratio of HCA to EDC is 1:2 to 1:5; the mass ratio of HCA to QCS is 1:5 to 3:5.
[0018] Furthermore, the mass ratio of the QCCS to blue cloth is 4:1 to 1:1.
[0019] Furthermore, the natural polysaccharide powder in step 9) is chitosan powder or starch powder.
[0020] The inventive principle of the present invention is:
[0021] Lanbuzheng is a traditional Chinese medicine that has the effects of invigorating qi and strengthening the spleen, nourishing blood and yin, moistening the lungs and resolving phlegm. Modern molecular biology and pharmacology have confirmed that the ingredients of Lanbuzheng include tannins, terpenes, flavonoids and phenylpropanoid compounds, etc., which have sedative, anti-inflammatory, and angiogenesis-promoting effects. It is a good medicine for promoting tissue regeneration and repair. At present, Lanbuzheng toothpaste has been used to treat oral diseases, and it has been found that it has excellent gum regeneration effects. It usually takes 3 months of continuous use to significantly observe gum regeneration. During brushing, Lanbuzheng has a short contact time with the gums and a small amount of residue, so it takes a long time to promote gum regeneration and repair. Moreover, Lanbuzheng itself does not have film-forming properties and cannot be prepared into film-like samples. There is no Lanbuzheng-related gum repair membrane product available.
[0022] Chitosan is the only weakly alkaline polysaccharide in nature, containing a large number of amino and hydroxyl groups, with abundant and easily available raw materials, and has excellent film-forming properties, and has been widely used in the biomedical field. The present invention compounds the blue button drug in a natural polysaccharide matrix to make a gum film, which achieves the purpose of adhering to the gums and slowly releasing blue button, thereby promoting the regeneration and repair of gum tissue, and has good application prospects in the field of oral medicine.
[0023] The beneficial effects of the present invention are:
[0024] Gum atrophy is a common oral disease, and more than 50% of people have gum atrophy problems. Severe gum atrophy can lead to tooth loss, which has caused great trouble to people's healthy life. Therefore, a natural polysaccharide / blue cloth gingival film with antibacterial and adhesive properties is prepared, which not only has good adhesion and antibacterial properties to wet gingival tissue, but also can promote angiogenesis and gingival repair, and has important clinical application value. The present invention generates chitosan quaternary ammonium salt by reacting the epoxy group in the 2,3-epoxypropyl-trimethylammonium chloride molecule with the amino group in the chitosan molecule, and the chitosan quaternary ammonium salt has a good inhibitory effect on the growth of oral bacteria that cause periodontitis, preventing oral bacteria from further damaging the gingival tissue. The carboxyl group in the 3,4-dihydroxyphenylpropionic acid molecule and the amino group in the chitosan molecule are catalyzed by N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, so that the chitosan macromolecule is linked to the catechol functional group, and the catechol can increase the adhesion performance of the material to the wet tissue, so that the oral film is not easy to fall off. After the QCCS / Lanbuzheng aqueous solution is cast into a film, it is dried to a semi-dry state, and then a layer of natural polysaccharide powder is evenly sprinkled on the upper surface of the film, and then it is dried. At this time, the natural polysaccharide-Lanbuzheng oral film prepared has an asymmetric structure. The side without natural polysaccharide powder is easy to adhere to the wet gingival tissue due to the presence of catechol structure, while the side sprinkled with natural polysaccharide powder can avoid the film sticking to the fingers when applying, which is convenient for clinical use. The Lanbuzheng drug is compounded in the natural polysaccharide matrix, and after adhering to the gums, Lanbuzheng can be slowly released, which promotes blood vessel regeneration and gingival tissue repair for a long time. The natural polysaccharide / Lanbuzheng gingival film has excellent oral harmful bacteria inhibition performance (bacterial inhibition rate of 99.9%) and wet gingival tissue adhesion performance (wet bonding strength ≥10kPa), Lanbuzheng drug sustained release time is up to 12 hours, which effectively promotes gingival regeneration and repair, and the asymmetric structure is also convenient for clinical application, and has good application prospects in the field of oral medicine. DETAILED DESCRIPTION
[0025] The present invention is further described below with reference to specific embodiments.
[0026] Embodiment 1:
[0027] 1) Weigh 2 g of chitosan (CS) powder and add it into 100 mL of 1% acetic acid aqueous solution, and stir for 0.5 hour to prepare a chitosan solution;
[0028] 2) Weigh 1.2 g of 2,3-epoxypropyl-trimethylammonium chloride, dissolve it in 10 mL of deionized water, and add it dropwise to the solution in 1) above, stir at 50°C for 6 h;
[0029] 3) placing the reaction product solution in 2) into a dialysis bag with a molecular weight cutoff of 3000, dialyzing for 3 days, replacing the dialysate once every 12 hours, and freeze-drying to obtain chitosan quaternary ammonium salt (QCS);
[0030] 4) adding 2 g of chitosan quaternary ammonium salt into 100 mL of deionized water and stirring for 0.5 hour to obtain a chitosan quaternary ammonium salt aqueous solution;
[0031] 5) 0.4 g of 3,4-dihydroxyphenylpropionic acid (HCA) and 0.8 g of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC) were dissolved in 10 mL of deionized water, and the solutions were added to the solution in 4) in sequence.
[0032] 6) The pH value of the solution in 5) was adjusted to 5.5 with hydrochloric acid solution, and then stirred at room temperature for 18 hours.
[0033] 7) The reaction product solution in 6) above is placed in a dialysis bag with a molecular weight cutoff of 3000, dialyzed for 3 days, the dialysate is replaced once every 12 hours, and freeze-dried to obtain catechol-modified chitosan quaternary ammonium salt (QCCS);
[0034] 8) Add 4 g QCCS and 1 g blue cloth into 100 mL deionized water and stir for 0.5 hours to prepare a QCCS / blue cloth aqueous solution;
[0035] 9) Pour the solution in 8) into a polytetrafluoroethylene mold (10cm×10cm×2mm), put it in a 60℃ oven for 1.5h, at which time the film is in a semi-dry state, sprinkle a layer of chitosan powder evenly on the upper surface of the film, and continue to put it in a 60℃ oven for 4h to obtain a natural polysaccharide / blue cloth orthodontic gingival film with antibacterial and adhesive properties. The natural polysaccharide / blue cloth orthodontic gingival film has excellent oral harmful bacteria inhibition performance (bacterial inhibition rate of 99.9%) and wet gingival tissue adhesion performance (wet bonding strength 12kPa), the blue cloth drug sustained release time is up to 12 hours, effectively promotes gingival regeneration and repair, and the asymmetric structure is also convenient for clinical application.
[0036] Embodiment 2:
[0037] 1) Weigh 5 g of chitosan (CS) powder and add it into 100 mL of 2% acetic acid aqueous solution, and stir for 40 min to prepare a chitosan solution;
[0038] 2) Weigh 5 g of 2,3-epoxypropyl-trimethylammonium chloride, dissolve it in 10 mL of deionized water, and add it dropwise to the solution in 1) above, stir at 60°C for 8 h;
[0039] 3) placing the reaction product solution in 2) into a dialysis bag with a molecular weight cutoff of 5000, dialyzing for 3 days, replacing the dialysate once every 12 hours, and freeze-drying to obtain chitosan quaternary ammonium salt (QCS);
[0040] 4) adding 5 g of chitosan quaternary ammonium salt into 100 mL of deionized water and stirring for 40 min to obtain a chitosan quaternary ammonium salt aqueous solution;
[0041] 5) 2 g of 3,4-dihydroxyphenylpropionic acid (HCA) and 6 g of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC) were dissolved in 20 mL of deionized water, and the solutions were added to the solution in 4) in sequence.
[0042] 6) The pH value of the solution in 5) was adjusted to 5.5 with hydrochloric acid solution, and then stirred at room temperature for 20 hours.
[0043] 7) The reaction product solution in 6) above is placed in a dialysis bag with a molecular weight cutoff of 5000, dialyzed for 3 days, the dialysate is replaced once every 12 hours, and freeze-dried to obtain catechol-modified chitosan quaternary ammonium salt (QCCS);
[0044] 8) Add 3 g QCCS and 1 g blue cloth into 50 mL deionized water and stir for 40 min to prepare a QCCS / blue cloth aqueous solution;
[0045] 9) Pour the solution in 8) into a polytetrafluoroethylene mold (10cm×10cm×2mm), put it in a 70℃ oven and bake it for 1.5h. At this time, the film is in a semi-dry state. Sprinkle a layer of starch powder evenly on the upper surface of the film, and continue to bake it in a 70℃ oven for 5h to obtain a natural polysaccharide / blue cloth orthodontic gingival film with antibacterial and adhesive properties. The natural polysaccharide / blue cloth orthodontic gingival film has excellent oral harmful bacteria inhibition performance (antibacterial rate of 99.9%) and wet gingival tissue adhesion performance (wet bonding strength 15kPa). The sustained release time of blue cloth is up to 12 hours, which effectively promotes gingival regeneration and repair, and the asymmetric structure is also convenient for clinical application.
[0046] Embodiment 3:
[0047] 1) Weigh 5 g of chitosan (CS) powder and add it into 50 mL of 5% acetic acid aqueous solution, and stir for 1 hour to prepare a chitosan solution;
[0048] 2) Weigh 10 g of 2,3-epoxypropyl-trimethylammonium chloride, dissolve it in 10 mL of deionized water, and add it dropwise to the solution in 1) above, stir at 80°C for 10 h;
[0049] 3) placing the reaction product solution in 2) into a dialysis bag with a molecular weight cutoff of 8000, dialyzing for 3 days, replacing the dialysate once every 12 hours, and freeze-drying to obtain chitosan quaternary ammonium salt (QCS);
[0050] 4) adding 5 g of chitosan quaternary ammonium salt to 50 mL of deionized water and stirring for 1 hour to obtain a chitosan quaternary ammonium salt aqueous solution;
[0051] 5) 3 g of 3,4-dihydroxyphenylpropionic acid (HCA) and 15 g of N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC) were dissolved in 30 mL of deionized water, and the solutions were added to the solution in 4) in sequence.
[0052] 6) The pH value of the solution in 5) was adjusted to 5.5 with hydrochloric acid solution, and then stirred at room temperature for 24 hours.
[0053] 7) The reaction product solution in 6) above is placed in a dialysis bag with a molecular weight cutoff of 8000, dialyzed for 3 days, the dialysate is replaced once every 12 hours, and freeze-dried to obtain catechol-modified chitosan quaternary ammonium salt (QCCS);
[0054] 8) Add 5 g QCCS and 5 g blue cloth into 100 mL deionized water and stir for 1 hour to prepare a QCCS / blue cloth aqueous solution;
[0055] 9) Pour the solution in 8) into a polytetrafluoroethylene mold (10cm×10cm×2mm), put it in an oven at 80°C for 1.5 hours, at which time the film is in a semi-dry state, sprinkle a layer of starch powder evenly on the upper surface of the film, and continue to put it in an oven at 80°C for 6 hours to obtain a natural polysaccharide / blue cloth orthodontic gingival film with antibacterial and adhesive properties. The natural polysaccharide / blue cloth orthodontic gingival film has excellent oral harmful bacteria inhibition performance (antibacterial rate of 99.9%) and wet gingival tissue adhesion performance (wet bonding strength 13kPa), the blue cloth drug sustained release time is up to 12 hours, effectively promotes gingival regeneration and repair, and the asymmetric structure is also convenient for clinical application.
Claims
1. A method for preparing a natural polysaccharide / blue cloth orthogingival film with antibacterial and adhesive properties, characterized in that: The specific steps are as follows: 1) adding chitosan powder to an acetic acid aqueous solution with a concentration of 1% to 5%, stirring for 0.5 to 1 hour to obtain a chitosan solution with a chitosan mass concentration of 20-100 mg / ml; 2) dissolving 2,3-epoxypropyl-trimethylammonium chloride in deionized water, and adding dropwise to the solution obtained in step 1), stirring at 50-80° C. for 6-10 hours; 3) placing the reaction product solution in step 2) into a dialysis bag with a molecular weight cutoff of 3000-8000D, dialyzing for 3 days, replacing the dialysate once every 12 hours, and freeze-drying to obtain chitosan quaternary ammonium salt (QCS); 4) adding QCS to deionized water and stirring for 0.5 to 1 hour to obtain a chitosan quaternary ammonium salt aqueous solution with a mass concentration of 20-100 mg / ml; 5) dissolving 3,4-dihydroxyphenylpropionic acid (HCA) and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC) in deionized water respectively, and adding the solutions to the solution obtained in step 4) in sequence; 6) adjusting the pH value of the solution obtained in step 5) to 5.5 with hydrochloric acid solution, and then stirring at room temperature for 18-24 hours; 7) The reaction product solution in step 6) is placed in a dialysis bag with a molecular weight cutoff of 3000-8000D, dialyzed for 3 days, the dialysate is replaced once every 12 hours, and freeze-dried to obtain catechol-modified chitosan quaternary ammonium salt (QCCS); 8) Add QCCS and indigoferin into deionized water and stir for 0.5 to 1 hour to prepare a QCCS / indigoferin aqueous solution, wherein the total mass concentration of QCCS and indigoferin is 50-100 mg / ml; 9) Pour the solution obtained in step 8) into a polytetrafluoroethylene mold and bake it in a 60-80°C oven for 1.5 hours. At this time, the film is in a semi-dry state. Sprinkle a layer of natural polysaccharide powder evenly on the upper surface of the film, and continue to bake it in a 60-80°C oven for 4-6 hours to obtain a natural polysaccharide / blue cloth orthogingival film with antibacterial and adhesive properties.
2. The method for preparing the natural polysaccharide / blue cloth orthogingival film with antibacterial and adhesive properties according to claim 1, characterized in that: The molecular weight of the chitosan is 10,000-1,000,000, and the deacetylation degree is 70%-95%.
3. The method for preparing the natural polysaccharide / blue cloth orthogingival film with antibacterial and adhesive properties according to claim 1, characterized in that: The mass ratio of 2,3-epoxypropyl-trimethylammonium chloride to chitosan is 0.6:1-2:
1.
4. The method for preparing the natural polysaccharide / blue cloth orthogingival film with antibacterial and adhesive properties according to claim 1, characterized in that: The mass ratio of HCA to EDC in step 5) is 1:2 to 1:5; the mass ratio of HCA to QCS is 1:5 to 3:
5.
5. The method for preparing the natural polysaccharide / blue cloth orthogingival film with antibacterial and adhesive properties according to claim 1, characterized in that: The mass ratio of QCCS to blue cloth described in step 8) is 4:1 to 1:
1.
6. The method for preparing the natural polysaccharide / blue cloth orthogingival film with antibacterial and adhesive properties according to claim 1, characterized in that: The natural polysaccharide powder described in step 9) is chitosan powder or starch powder.
7. A natural polysaccharide / blue cloth orthodontic gingival film with antibacterial and adhesive properties, characterized in that: The method is prepared by the method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Composition for improving oral hygiene and preventing and treating oral diseases and preparation method
CN107397805A
Chitosan-based hydrogel, and preparation method and application thereof
CN109381738A
Preparation method of multifunctional hydrogel for treating periodontal tissue inflammatory destruction
CN115154672A
A chitosan membrane comprising catechol groups and preparation method thereof
KR101942220B1
Tissue adherent chitosan material that resists dissolution
US20210060203A1